Ancient brews : rediscovered and re-created - McGovern, Patrick E. (W.W. Norton & Company, 2018)
Interweaving archaeology and science, Patrick E. McGovern tells the enthralling story of the world's oldest alcoholic beverages and the cultures that created them. Humans invented heady concoctions, experimenting with fruits, honey, cereals, tree resins, botanicals, and more. These "liquid time capsules" carried social, medicinal, and religious significance with far-reaching consequences for our species. McGovern describes nine extreme fermented beverages of our ancestors, including the Midas Touch from Turkey and the 9000-year-old Chateau Jiahu from Neolithic China, the earliest chemically identified alcoholic drink yet discovered. For the adventuresome, homebrew interpretations of the ancient drinks are provided, with matching meal recipes.